2021
DOI: 10.3390/ijerph18052515
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, Acceptability, and Outcomes of a Yoga-Based Meditation Intervention for Hospice Professionals to Combat Burnout

Abstract: (1) Background. This research examined the feasibility, acceptability and outcomes of delivering a 6-week yoga-based meditation intervention to clinical teams of hospice professionals (HPs) at a large non-profit hospice organization. The intervention was designed to increase mind-body integration and combat burnout. This article was written for different audiences, including research scientists who study interoception, burnout, meditation, or yoga, designers of meditation interventions, and hospice organizatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…On the full-text screening, fifteen non-clinical studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], four non-intervention studies [ 40 , 41 , 42 , 43 ], three generic studies [ 44 , 45 , 46 ], five studies not using MBMs [ 47 , 48 , 49 , 50 , 51 ], and one not presenting evaluation results [ 52 ] were excluded. Ultimately, this review included 18 studies [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the full-text screening, fifteen non-clinical studies [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ], four non-intervention studies [ 40 , 41 , 42 , 43 ], three generic studies [ 44 , 45 , 46 ], five studies not using MBMs [ 47 , 48 , 49 , 50 , 51 ], and one not presenting evaluation results [ 52 ] were excluded. Ultimately, this review included 18 studies [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 16 [ 53 , 54 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 ] were published articles and 2 [ 55 , 67 ] were conference abstracts. Researchers from nine countries conducted these studies, and the study conducted in the United States was the most common, with six studies [ 54 , 55 , 59 , 60 , 63 , 68 ], followed by India with three studies [ 56 , 57 , 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, several clinical trials have suggested the promise of yoga intervention as an adjunct therapy for patients with OCD, who were unresponsive to conventional treatments[ 208 , 209 ]. Moreover, yoga training enhanced general satisfaction, improved work exhaustion, and led to greater work engagement and empathy among teachers[ 210 ], nurses[ 211 ], hospice professionals[ 212 ], and physicians[ 213 , 214 ], who were suffering from job burnout. Yoga can promote the psychological and physical well-being of subjects with burnout, particularly when combining it with other activities, such as art and music-therapy[ 215 , 216 ].…”
Section: The Clinical Effect Of Yogamentioning
confidence: 99%